ReXcor: a model of the X-ray spectrum of active galactic nuclei that combines ionized reflection and a warm corona. Issue 1 (15th June 2022) - Xiang, X; Ballantyne, D R; Bianchi, S; De Rosa, A; Matt, G; Middei, R; Petrucci, P-O; Różańska, A; Ursini, F
ABSTRACT: The X-ray spectra of active galactic nuclei (AGNs) often exhibit an excess of emission above the primary power law at energies ≲2 keV. Two models for the origin of this 'soft excess' are ionized relativistic reflection from the inner accretion disc and Comptonization of thermal emission in a warm corona. Here, we introduce reXcor, a new AGN X-ray (0.3–100 keV) spectral fitting model that self-consistently combines the effects of both ionized relativistic reflection and the emission from a warm corona. In this model, the accretion energy liberated in the inner disc is distributed between a warm corona, a lamppost X-ray source, and the accretion disc. The emission and ionized reflection spectrum from the inner 400  rg of the disc is computed, incorporating the effects of relativistic light-bending and blurring. The resulting spectra predict a variety of soft excess shapes and sizes that depend on the fraction of energy dissipated in the warm corona and lamppost. We illustrate the use of reXcor by fitting to the joint XMM–Newton and NuSTAR observations of the Seyfert 1 galaxies HE 1143-1820 and NGC 4593, and find that both objects require a warm corona contribution to the soft excess. Eight reXcor table models, covering different values of accretion rate, lamppost height, and black hole spin, are publicly available through the xspec website. Systematic use of reXcor will provide insight into the distribution of energy in AGN accretion flows.